2006
DOI: 10.1158/1078-0432.ccr-06-0021
|View full text |Cite|
|
Sign up to set email alerts
|

Focal Adhesion Kinase Targeting Using In vivo Short Interfering RNA Delivery in Neutral Liposomes for Ovarian Carcinoma Therapy

Abstract: Purpose: Focal adhesion kinase (FAK) plays a critical role in ovarian cancer cell survival and in various steps in the metastatic cascade. Based on encouraging in vitro results with FAK silencing, we examined the in vivo therapeutic potential of this approach using short interfering RNA (siRNA) in the neutral liposome 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine (DOPC). Experimental Design:Therapy experiments of FAK siRNA with or without docetaxel were done using human ovarian cancer cell lines SKOV3ip1, HeyA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
205
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(213 citation statements)
references
References 47 publications
8
205
0
Order By: Relevance
“…Early studies in ovarian cancer cell lines and xenografts demonstrated that knockdown of FAK expression enhanced docetaxel efficacy in docetaxelsensitive and docetaxel-resistant models in vitro and in vivo (31,32). Subsequently, TAE226, a TKI that targets FAK and IGF-1R, was demonstrated to enhance docetaxel cytotoxicity (33); however, at this point, development stalled due to the drug failing clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in ovarian cancer cell lines and xenografts demonstrated that knockdown of FAK expression enhanced docetaxel efficacy in docetaxelsensitive and docetaxel-resistant models in vitro and in vivo (31,32). Subsequently, TAE226, a TKI that targets FAK and IGF-1R, was demonstrated to enhance docetaxel cytotoxicity (33); however, at this point, development stalled due to the drug failing clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches include the various small molecule inhibitors and FAK silencing using FAK targeted short interfering RNA (siRNA). 34,35 Recently, VS-6062 was the first-in-class FAK inhibitor to enter phase I dose-escalation trials in advanced, terminal solid malignancies. Disease stability (≥ six 21 d cycles) was observed in 15 of 91 patients (16%) with measurable disease, which is noteworthy for a heavily pre-treated population.…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell lysate for western blot analysis of FAK and pFAK Y397 expression was prepared as previously reported. 35 Proteins were separated by 7.5% SDS-PAGE and transferred to nitrocellulose membrane. Membranes were blocked with 5% nonfat milk and incubated with anti-pFAK Y397 antibody (1:1000, BD Transduction Laboratories) for 1 h at room temperature.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…In ovarian cancer patients, FAK overexpression is associated with aggressive tumor features resulting to poor overall survival. 79 In this regard, systemic targeting of FAK with liposomal NPs or small molecule inhibitors has shown reduction in tumor growth and metastasis, 77,80 but such approaches are not tumor-specific and could result in undesired side effects. This highlights the need for targeted delivery of these therapeutic molecules.…”
Section: Stat3 Silencing In Dendritic Cellsmentioning
confidence: 99%